2015
DOI: 10.1007/s11552-015-9771-x
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Ultrasound for Diagnosing Purulent Infections of the Upper Extremity

Abstract: Diagnostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Previous studies have established the diagnostic strength of MSK-US for superficial soft tissue abscess formation. These studies showed different values, sensitivity 98% and specificity 88%, 18 96.7% and 85.7%, 19 97% and 83%, 20 and, 65.9% and 94%, 21 respectively. Comparing those with the study results, the calculated sensitivity of 92% (vs improved laboratory parameters) and 100% (vs intraoperative findings) was comparable with the sensitivity established by three of the four studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies have established the diagnostic strength of MSK-US for superficial soft tissue abscess formation. These studies showed different values, sensitivity 98% and specificity 88%, 18 96.7% and 85.7%, 19 97% and 83%, 20 and, 65.9% and 94%, 21 respectively. Comparing those with the study results, the calculated sensitivity of 92% (vs improved laboratory parameters) and 100% (vs intraoperative findings) was comparable with the sensitivity established by three of the four studies.…”
Section: Discussionmentioning
confidence: 89%
“…1,8 Previous studies have established the sensitivity and specificity of sonography in detecting skin and superficial soft tissue abscess formation. [18][19][20][21] However, the sensitivity and specificity of sonography for detecting abscesses in deeper soft tissues and muscle, particularly pyomyositis, have not been described.…”
mentioning
confidence: 99%
“…But B-mode ultrasound and duplex ultrasound have limitations: Evaluation can be difficult in cases when pus presents with the same echogenicity as lymphatic tissue and can therefore be hardly distinguished. It is also artifact-prone especially to movement or in the evaluation of structures in deep tissue regions, which is true especially concerning duplex ultrasound [4,5]. New ultrasound techniques like superb microvascular imaging (which has proven to be able to detect low-grade inflammation) or B-flow imaging have, to our knowledge, not yet been assessed for their suitability for the detection of peritonsillar abscess [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Focused Abdominal Series for Trauma (FAST) has revolutionized the manner in which abdominal trauma is safely and noninvasively identified and rapidly screened for possible operative intervention 4 . Within orthopaedics, ultrasound has already been successfully used to aid diagnosis of upper extremity abscesses 5, 6 as well as identify rotator cuff tears 7, 8 .…”
Section: Introductionmentioning
confidence: 99%